A case of exceptional reading accuracy in a child with Down syndrome: Underlying skills and the relation to reading comprehension. - Groen, M; Laws, G; Nation, K; Bishop, D (2006)
We report on a case of a girl with Down syndrome (DS), K.S., whose reading accuracy is exceptional. This ability is associated with robust phonological skills and relative strengths in visual and verbal short-term memory, articulation, and speech fluency. Although her reading comprehension is age appropriate when it comes to the retention of literal information, K.S. has some difficulties in using knowledge-based inferences in reading comprehension. Reading comprehension in that sense is at a level commensurate with her oral language skills. Her reading performance parallels that of children with reading comprehension difficulties who do not have DS. This reading profile is in contrast with claims that individuals with DS mainly use sight-word strategies in reading and shows that the phonological pathway can be highly proficient in a child with DS. However, even in a case such as K.S. where reading accuracy is good, functional literacy is constrained by limited comprehension skills.